2007
DOI: 10.1259/bjr/17112059
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cerebral blood volume maps generated fromT2* andT1weighted MRI data in intra-axial cerebral tumours

Abstract: Type of Manuscript: ORIGINAL RESEARCH ABSTRACTPurpose: To compare parametric maps, measured values and value distributions of cerebral blood volume (CBV) derived from 1) first pass T 1 -weighted dynamic contrast-enhanced (DCE) data (T 1 -CBV) and 2) T 2 *-weighted DCE data (T 2 *-CBV) in patients with intraaxial tumours. Materials and Methods: Sequential T 1 -and T 2 *-weighted DCE-MRI acquisitions were performed in 9 patients with cerebral neoplasms. CBV maps were calculated from T 2 *-weighted data using a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
22
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 39 publications
2
22
0
Order By: Relevance
“…This difference has been shown by several groups. 15,16 Our results are, therefore, consistent with their hypothesis of blood volume overestimation when the DCE-T1 approach is used and underestimation when the DSC-T2 method is used. This mismatch is thought to be caused by contrast leakage.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This difference has been shown by several groups. 15,16 Our results are, therefore, consistent with their hypothesis of blood volume overestimation when the DCE-T1 approach is used and underestimation when the DSC-T2 method is used. This mismatch is thought to be caused by contrast leakage.…”
Section: Discussionsupporting
confidence: 89%
“…Visual inspection revealed coregistration not completely accurate between K trans and CBV maps, mostly due to spatial distortions resulting from susceptibility effects in the T2*WI acquisition. Haroon et al 16 reported the same problem when trying to correlate CBV derived from T1 and T2* sequences in brain tumors. Correlation between the 2 estimates of microvascular density (CBV and VP) is also significant and stronger than that between K trans and CBV and K trans and VP.…”
Section: Discussionmentioning
confidence: 98%
“…Ludemann et al 16 compared DCE-and DSCderived CBV values in intra-axial tumors with no baseline T1 measurements and found a borderline correlation (P value between 0.1 and 0.05). Haroon and al 15 found a good correlation (r ϭ 0.667, P Ͻ .05) between DSC-and DCE-derived CBV in intra-axial tumors by using a method with baseline T1 calculation.…”
Section: Discussionmentioning
confidence: 94%
“…13,14 To our knowledge, there have been few comparative studies between DCE and DSC imaging in patients with gliomas. 15,16 The main objective of our study was to compare the diagnostic accuracy of DCE-MR imaging with DSC-MR imaging in the preoperative grading of astrocytomas at 3T by using a high-relaxivity agent. For DCE-MR imaging analysis, we performed 2 different methods: 1) using phase-derived VIF with bookend T1 measurements; and 2) using magnitude-derived VIF without T1 mapping.…”
mentioning
confidence: 99%
“…As mentioned before, accurate Ktrans evaluation is needed because it may have an influence on vp calculation and consequently, vb values [21]. Haroon et al [41] also compared the T2*-DSC and T1-DCE CBV and found a moderate correlation between these two techniques (ρ = 0.667, p<0.05), but their study group was very small, and different grades of glioma and other types of intra-axial tumors were not compared separately. In addition, their ROIs were placed on the entire enhanced part of the lesion and a different algorithm was used to analyze their images.…”
Section: Discussionmentioning
confidence: 99%